Analisis Framing Pesan Moral Dalam Film Weeding Agreement - Nadiya, Afidhah (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2022)
This paper aims to find out in depth the systematics of the presentation and content of the story and to find the moral messages contained in the Wedding Agreement Film. The research method uses a qualitative approach and the Zhongdang Pan and Gerald M. Kosicki's framing analysis model with data collection through documentation on the film, the data obtained is then analyzed through the framing structure, namely syntactic, script, thematic and rhetorical according to the message issues highlighted in the frames shown. contained in the film. by presenting data by emphasizing certain parts, highlighting certain aspects, and enlarging how to tell stories from an event. The results of this study indicate the existence of framing and moral messages conveyed in the film. The moral messages found in this film have three aspects, namely moral messages towards God, morals towards oneself, and morals towards others and the environment. Keywords : Messages, Moral, Film